2016
DOI: 10.1177/0040517516639816
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in skin-contact clothes and migration to artificial sweat: Risk assessment of human dermal exposure

Abstract: The concentrations of a considerable number of trace elements (Ag, Al, As, B, Ba, Be, Bi, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Mo, Ni, Pb, Sb, Sc, Se, Sm, Sn, Sr, Ti, Tl, V and Zn) were determined in various skin-contact clothes (T-shirts, blouses, socks, baby pajamas and bodies) from the Catalan (Spain) market. In addition, migration experiments with artificial acidic sweat were conducted in order to establish the migration rates of these elements. High levels of Zn (186-5749 mg/kg) were found in zinc pyrithione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Chemicals that have been identified on newly purchased clothing include trace elements such as heavy metals; residual aromatic amines associated with certain azo dyes; , quinoline and substituted quinolines; alkylphenol ethoxylates, alkylphenols, bisphenols, and benzophenones; , benzothiazoles and benzotriazoles, , dioxins and furans; PCBs; , organo-phosphorus flame retardants and pesticides; halogenated flame retardants; ,, fluorinated surfactants; phthalate ester plasticizers; , glycol solvents; formaldehyde from antiwrinkle resins; ,,, and common petrochemical fuel constituents such as linear and branched C 10 –C 16 alkanes, C 3 alkylbenzenes, and straight-chained C 7 –C 10 aldehydes …”
Section: Chemical Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals that have been identified on newly purchased clothing include trace elements such as heavy metals; residual aromatic amines associated with certain azo dyes; , quinoline and substituted quinolines; alkylphenol ethoxylates, alkylphenols, bisphenols, and benzophenones; , benzothiazoles and benzotriazoles, , dioxins and furans; PCBs; , organo-phosphorus flame retardants and pesticides; halogenated flame retardants; ,, fluorinated surfactants; phthalate ester plasticizers; , glycol solvents; formaldehyde from antiwrinkle resins; ,,, and common petrochemical fuel constituents such as linear and branched C 10 –C 16 alkanes, C 3 alkylbenzenes, and straight-chained C 7 –C 10 aldehydes …”
Section: Chemical Exposuresmentioning
confidence: 99%
“…130 Models of sweat-mediated transfer of chemicals from clothing also use a transfer efficiency approach. The leachable fraction is derived from experiments using artificial sweat to extract substances such as dyes 17,43 and trace elements 57 (see also Section 3.1.3). Often, the extracted fraction is assumed to be entirely transferred to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the concentrations measured in textiles represent only the solvent-extractable fraction of the chemicals from textiles, which may not represent the actual amount present in textiles. The actual concentration may be higher than what was extracted by organic solvents, while the bioavailable fraction may be lower (Rezic and Steffan, 2007;Rovira et al, 2017). Third, the exposure assessment in this study was based on certain assumptions regarding dermal penetration rate and body surface area, and selected worst-case scenarios for exposure were employed.…”
Section: Dermal Exposure To Bths and Btrs Via Textilesmentioning
confidence: 99%
“…In a recent report alerting consumers to dangerous chemicals in products from the European Union, 572 chemical-related notifications involving toys (37%), jewelry (20%) and clothing and textiles (13%) were identified (Chemical Watch, 2016). Other recent studies reported the occurrence of benzothiazoles (BTHs) and benzotriazoles (BTRs) in textiles from Sweden (Avagyan et al, 2015) and toxic metals in textiles from Spain (Rovira et al, 2015;Sungur and Gülmez, 2015;Rovira et al, 2017). A report by Greenpeace showed the presence of a wide range of endocrine disrupting chemicals in textiles, with nonylphenol ethoxylate concentrations as high as 17,000 μg/g (Greenpeace, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These metals are prone to migrate onto the human skin under sweating or wet condition. According to previous investigation, depending on the migration rate of trace elements, several skin and other diseases can be occurred which were studied by dermal exposure through the skin-contact clothes (Rovira et al 2016;Von Goetz et al 2013;Avagyan et al 2015;Leme et al 2014;Sengupta and Behera 2014;Clausen et al 2016). Averagely, the detected trace metals are typically migrated ranging 0.6-60% (Tuzen et al 2008).…”
Section: Level Of Trace Metals In the Finished Fabricmentioning
confidence: 99%